Contributions of Subjective Well-Being and Good Living to the Contemporary Development of the Notion of Sustainable Human Development - Castillo-Guajardo, D (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The article analyzes the contributions of the notions of Good Living attributable to episte-mologies, traditions, and subjective well-being at work, given the current changes in the working context, to enrich the concept of human development. The article is developed with an analytical-descriptive and synthetic approach, reconstructing the concept of Good Living through a theoretical-economic, ontological, and epistemological comparison and its dimensional axes. Methodologically, a systematic review of human development literature is used in Latin America through the Web of Science (WOS), comparing the UNDP Technical Notes (HDI) with the various approaches to Good Living published between 2010 and 2020. These documents were subjected to semantic contrast, with reference to the various dimensions and positions of human development as a generator of subjective well-being for the configuration of public labor policies. The main findings refer to the disagreement points evidenced in the two-axes dimensions of the Good Living measurement systems (mobility and safety, and cultural satisfaction within territories), an important factor being the sumak kawsay, the concept of Good Living. Sumak is fullness, the sublime, excellent, magnificent, beautiful, superior. Kawsay is life, being. However, it is dynamic, changing, and is not a passive question, and is thus not considered by the different evolutionary changes of the HDI. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.